2013
DOI: 10.1189/jlb.0812431
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for Rab27a GTPase in eosinophil exocytosis

Abstract: Eosinophil degranulation has been implicated in inflammatory processes associated with allergic asthma. Rab27a, a Rab-related GTPase, is a regulatory intracellular signaling molecule expressed in human eosinophils. We postulated that Rab27a regulates eosinophil degranulation. We investigated the role of Rab27a in eosinophil degranulation within the context of airway inflammation. Rab27a expression and localization in eosinophils were investigated by using subcellular fractionation combined with Western blot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
(74 reference statements)
1
26
0
Order By: Relevance
“…Given that recipient I5/hE2/EPX −/− mice lacked endogenous EPX expression, EPX release detected in BALs from recipient mice derived solely from intratracheally transferred peripheral blood eosinophils isolated from eoCRE/I5/EPX +/+ or eoCRE/V7/I5/EPX +/+ mice (Fig. 4a), using our previously reported model 19 . Using this adoptive transfer model, both eoCRE/I5/EPX +/+ - and eoCRE/V7/I5/EPX +/+ -derived eosinophils exhibited degranulation to endogenous signals in I5/hE2/EPX −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Given that recipient I5/hE2/EPX −/− mice lacked endogenous EPX expression, EPX release detected in BALs from recipient mice derived solely from intratracheally transferred peripheral blood eosinophils isolated from eoCRE/I5/EPX +/+ or eoCRE/V7/I5/EPX +/+ mice (Fig. 4a), using our previously reported model 19 . Using this adoptive transfer model, both eoCRE/I5/EPX +/+ - and eoCRE/V7/I5/EPX +/+ -derived eosinophils exhibited degranulation to endogenous signals in I5/hE2/EPX −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with various leukocytes have shown that Rab27A is involved in both exocytosis/secretion and endocytosis/phagocytosis303132. Rab27A-deficient neutrophils3334, eosinophils35, basophils36 all show impaired exocytosis. In contrast, receptor-mediated phagocytosis is enhanced in Rab27A-deficient macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…Third, when double labeling of CLC‐P and EPO was performed in eosinophils from the peripheral blood, the majority of the granules labeled for CLC‐P was also positive for EPO, a typical cationic protein stored in specific granules . Fourth, CLC‐P also colocalized with CD63, a member of the transmembrane‐4 glycoprotein superfamily (tetraspanins) (reviewed in), that is a marker for eosinophil specific granules …”
Section: On the Nomenclature And Composition Of Eosinophil Cytoplasmimentioning
confidence: 99%